Cesarean Section profile at a tertiary center - Shrestha, Madhu; Shrestha, Shanti (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aim: To determine the incidence and indication of caesarean section. Method: It is a retrospective cross sectional study conducted at Paropakar Maternity and Women’s Hospital for three months. The data was retrieved from the medical record of operation theatre. Results: During the study period, 31.1% (1,592 out of 5,120) of women underwent caesarean section. Eighty eight percent (n-1,402) of them were emergency caesarean section while 12 % were elective (n-190). Majority of the women (70.3%) belonged to 20-29 years and half of them were primigravida. Around 89.2% caesarean sections were performed at 37-42 weeks of gestation. The four leading indications were fetal distress (31.5%), previous caesarean section (19.7%), cephalo -pelvic disproportion (13.4%) and abnormal presentation (7.9%). Conclusions: In this study, incidence of caesarean section is more than WHO recommendation. It may be mainly due to the referral of complicated cases from the periphery of the country. Key words: caesarean section, indication